Type I Interferon Impairs Specific Antibody Responses Early during Establishment of LCMV Infection - Daugan, Matthieu; Murira, Armstrong; Mindt, Barbara C.; Germain, Amélie; Tarrab, Esther; Lapierre, Pascal; Fritz, Jörg H.; Lamarre, Alain (Frontiers in Immunology, 2016)
Elicitation of type I interferon (IFN-I) has been shown to both enhance and impair cell-mediated immune responses in acute and persistent viral infections, respectively. Here, we show that in addition to its effect on T cells, IFN-I drives impairment of specific antibody responses through interaction with B cells in the acute phase of lymphocytic choriomeningitis virus (LCMV) infection. This impairment was limited to the T cell-dependent B cell response and was associated with disruption of B cell follicles, development of hypergammaglobulinemia (HGG) and expansion of the T follicular helper cell population. Antigen-specific antibody responses were restored by ablation of IFN-I signaling through antibody-mediated IFN-I receptor blockade and B cell-specific IFN-I receptor knockout. Importantly, IFN-I receptor deficiency in B cells also accelerated the development of LCMV neutralizing antibodies and alleviated HGG. These results provide a potential therapeutic target towards efficient treatment measures that limit immunopathology in persistent viral infections.